Development of Discrete Mathematics Module Based on Discovery Learning for Mathematical Understanding in Higher Education - Amir, Almira; Adinda, Anita; Sutan, Tabrani; Siregar, Torang; Hariyani, Novita (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to develop a discrete mathematics module based on discovery learning to improve students’ mathematical understanding in higher education. This research used the Research and Development (R&D) method with a mixed approach and ADDIE model in the product development stage. The data collection techniques used questionnaires, tests and interview guides. Meanwhile, the data analysis technique used in this research combines qualitative and quantitative descriptive. The results include (1) Reviewing the study of discrete mathematics module development; it obtained valid results after going through several assessments and revisions, and the practicality of developing this discrete mathematics module was categorized as practical; it is not surprising that the module can increase students’ mathematical understanding with a range of 37.97; (2) Judging from effectiveness; it is obtained from inferential statistics that significance is 0.00, which means there is an influence on the use of discovery learning-based discrete mathematics modules on students’ mathematical understanding. These results have implications that the module has proved effective in improving students’ mathematical understanding in higher education.